Adenovirus-mediated human aquaporin-1 expression in hepatocytes improves lipopolysaccharide-induced cholestasis - Marrone, Julieta (2017)
Lipopolysaccharides (LPS) are known to cause cholestasis in sepsis. There is evidence that a defective expression of canalicular aquaporin water channels contributes to bile secretory failure in LPS-induced cholestasis. Thus, we studied whether the hepatic adenovirus-mediated transfer of human aquaporin-1 gene (haqp1) can improve the cholestasis induced by LPS. Adenoviral vector encoding hAQP1 (AdhAQP1) or control vector was administered to rats by retrograde intrabiliary infusion. Hepatocyte canalicular hAQP1 expression was assessed by liver immunostaining and immunoblotting in purified plasma membranes. LPS reduced bile flow and biliary bile acid excretion by 30% and 45%, respectively. AdhAQP1-treatment normalized both bile flow and biliary bile acid excretion in LPS-induced cholestasis. Moreover, markedly elevated serum bile acid levels in cholestatic rats, were also normalized with the AdhAQP1 hepatic transduction. Bile flow and serum or biliary bile acids in normal rats were not significantly altered by AdhAQP1. AdhAQP1 delivery unaffected the downregulated protein expression of canalicular bile salt export pump (BSEP/ABCB11) in cholestasis, but improved its transport activity restoring reduced canalicular cholesterol content. Our data suggest that the adenovirus-mediated hepatocyte hAQP1 expression improves LPS-induced cholestasis in rats by stimulating the BSEP/ABCB11-mediated biliary bile acid excretion; a finding that might contribute to the understanding and treatment of sepsis-associated cholestatic diseases.